2020
DOI: 10.1101/2020.06.23.167494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrient sensing in the nucleus of the solitary tract mediates non-aversive suppression of feeding via inhibition of AgRP neurons

Abstract: 10The nucleus of the solitary tract (NTS) is emerging as a major site of action for the appetite-suppressive 11 effects of leading pharmacotherapies currently investigated for the treatment of obesity. However, our 12 understanding of how NTS neurons regulate appetite remains incomplete. Here we used NTS nutrient 13 sensing as an entry point to characterize stimulus-defined neuronal ensembles engaged by the NTS to 14 produce physiological satiety. Using activity-dependent expression of genetically-encoded circ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Consistent with this possibility, it has been shown that several regions in the brainstem, including NTS, parabrachial nucleus, and periaqueductal gray matter, innervate the DMH (31). In addition, leucine-sensing NTS neurons also regulate food intake by sending projections to the DMH (32). Several brain regions in the hypothalamus also innervate the DMH, including preoptic (POA), paraventricular, and arcuate nuclei (31).…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with this possibility, it has been shown that several regions in the brainstem, including NTS, parabrachial nucleus, and periaqueductal gray matter, innervate the DMH (31). In addition, leucine-sensing NTS neurons also regulate food intake by sending projections to the DMH (32). Several brain regions in the hypothalamus also innervate the DMH, including preoptic (POA), paraventricular, and arcuate nuclei (31).…”
Section: Discussionmentioning
confidence: 88%
“…VTA circuits are also sensitive to the caloric content of food (de Araujo et al, 2008;Domingos et al, 2011;Beeler et al, 2012;Ferreira et al, 2012;McCutcheon et al, 2012a) and this information is relayed to forebrain regions controlling food-seeking behaviors (Tellez et al, 2016). Whether VTA neurons are sensitive to protein or amino acids directly is not known but individual amino acid levels can be detected by hypothalamic, cortical, and hindbrain regions connected to the VTA (Karnani et al, 2011;Anthony and Gietzen, 2013;Heeley and Blouet, 2016;Tsang et al, 2020). Furthermore, recent work showed that fibroblast growth factor 21 (FGF21), a hepatic hormone, is released in response to reduction in dietary protein (Laeger et al, 2014) and its central action is necessary for development of protein preference in mice (Hill et al, 2019).…”
Section: Discussionmentioning
confidence: 99%